To graph the equation x - y = 6 in the form y = mx + b, we can first rearrange the equation to solve for y:
x - y = 6
-y = -x + 6
y = x - 6
Now the equation is in the form y = mx + b where m is the slope and b is the y-intercept.
The slope (m) is 1, and the y-intercept (b) is -6.
Now we can graph the equation with a slope of 1 (meaning the line goes up 1 unit for every 1 unit to the right) and a y-intercept of -6 (where the line crosses the y-axis at y=-6).
Let's plot these points and draw the line:
y = x - 6
y-intercept: (0, -6)
x-intercept: (6, 0)
Now, we can connect these two points with a straight line to graph the equation x - y = 6 in the form y = mx + b.
Graphing Linear Equations Unit Test Graph the equation x - y = 6 using the form y = mx + b (1 point)
1 answer